Infection Prevention New Perspectives and Controversies (Springer International Publishing, 2018)
This book reviews evolving areas in infection prevention on topics including contact precautions, technology implementation, specific infections, and care in various settings. The book summarizes the current data on infection prevention, presents controversies on the various topics, and includes recommendations for patient safety. Addressing hot topics such as MRSA, C. difficile vaccination, mandatory flu vaccines, and CLABSI, this is the only text to include prevention and control overviews across a range of infection issues. Written by experts in the field, this book contains 32 chapters that educates and presents the most cutting-edge models of care on emerging and evolving topics in infectious diseases. Infection Prevention: New Perspectives and Controversies is a valuable resource for infection prevention professionals, healthcare quality and safety professionals, caring for patients in in- and outpatient settings.